Répertoire des œuvres des compositrices du Québec au XXe siècle - Labelle, Nicole (Centre de recherche en civilisation canadienne-française, 1997)
Document de travail
Keywords: 1900-1999; DIG; amériques; art; discipline; femmes* artistes; histoire des femmes*; histoire et politique; musique; périodes historiques; québec; ressource en ligne; régions géographiques; thématiques; travail

La critique féministe étatsunienne en musique : pertinence en milieu francophone Québécois - Sabourin, Carmen (Canadian University Music Review / Revue de musique des universités canadiennes, 1997)
L’auteure examine la pertinence de la critique féministe étasunienne en musique en milieu francophone québécois. Dans un premier temps, elle propose une réflexion critique sur le féminisme étasunien en musique. Puis, elle pose la question de la pertinence de ses fondements et de ses méthodologies pour les jeunes musicien(ne)s issus du milieu culturel francophone du Québec qui, au moment d’entreprendre des études avancées, envisageraient de se consacrer à la recherche sur la pensée féministe.
https://id.erudit.org/iderudit/1014823ar
Keywords: DIG; amérique du nord; amériques; arts; canada; discipline; débat; féminisme étasunien; musique; québec; ressource en ligne; régions géographiques; théories féministes

Creating worlds for my music to exist: How women composers of electroacoustic music make place for their voices - McCartney, Andra (Université York, 1994)
For this study, I have interviewed fourteen women composers of electroacoustic music in or near the three Canadian urban centres of Montreal, Toronto, and Vancouver. Montreal: Ciaire Pich6, Lucie Jasmin, Pascale Trudel, Monique Jean, Helen Hall and Kathy Kennedy; Toronto: Gayle Young, Sarah Peebles, Wende Bartley, Elma Miller, Ann Southam, and Carol Ann Weaver; Vancouver: Hildegard Westerkamp and Susan Frykberg. These interviews were all conducted between January and November of 1993. References to the development of electroacoustic music in Canada are sparse in the existing literature, both in general histories of electroacoustic music, and in histories of Canadian music. And even though there seem to be some areas of change (for instance, recent publications in Quebec), women composers are under-represented in writings and recorded collections of electroacoustic music in Canada. Chapter Two situates the work of women composers in the Canadian scene, discussing particularly the work of Norma Beecroft, Marcelle Desch§nes, Diana McIntosh, and Micheline Coulombe Saint-Marcoux. Chapter Three describes the metaphors, images and myths invoked in malestream discourses associated with electroacoustic music, in popular magazines, course texts and software. I investigate how my consultants’ language reflects and/or contests mainstream imagery, or how it might be framed by entirely different assumptions and experiences. Chapter Four is concerned with the institutional structures of electroacoustic music. I discuss how gendering exhibits itself in the division of labour in electroacoustic studio courses at universities, as well as in concert halls, conferences, and professional organizations. Excerpts from the interviews record my consultants experiences in these institutions, as students, teachers, and composers. In Chapter Five, I point out the variety of strategies that each composer uses to construct her identity within the world of electroacoustics. Each entry takes the form of a three or four page sketch, with quotes from the interview regarding the social environment, equipment choices, compositional styles, and particular pieces that my consultant discusses. Chapter Six discusses three pieces in detail: one by Susan Frykberg, Woman and House; one by Wende Bartley, A Silence Full of Sound; and one by Hildegard Westerkamp, Breathing Room. I focus on how each of the composers chooses to work with technology, and how her culturally-constructed position as a woman affects her work. I describe how my consultants imagine other stories to tell, and other possible lived social relations. The conclusions in Chapter Seven, in addition to suggesting areas for future research, discuss three themes that run throughout the study: the idea of gender as performance, the doubleness of my consultants' responses to technology, and the importance of the linguistic and musical metaphors that they use.
https://ocul-yor.primo.exlibrisgroup.com/permalink/01OCUL_YOR/j50f41/cdi_proquest_journals_304118103 Accès par ProQuest
Keywords: 1900-1999; 1990-1999; DIG; amériques; arts; canada; discipline; femmes* artistes; genre; montréal; musique; mémoires/thèses; périodes historiques; ressource en ligne; régions géographiques; toronto; vancouver

Existe-t-il une musique dite féministe ? - Lefebvre, Marie-Thérèse (Les bâtisseuses de la Cité : actes du Colloque Les Bâtisseuses de la Cité dans le cadre de la Section d'études féministes du Congrès de l'Acfas 1992, 1993)
https://cap.banq.qc.ca/notice?id=p%3A%3Ausmarcdef_0005389009&locale=fr
Keywords: 1600-1699; 1700-1799; 1900-1999; DIG; amérique du nord; amériques; arts; canada; discipline; femmes* artistes; histoire et politique; musique; périodes historiques; québec; ressource en ligne; régions géographiques; thématiques

La musique composée au féminin - Martin-Kostajnsek, Sylvaine (Les Bâtisseuses de la Cité : actes du Colloque Les Bâtisseuses de la Cité dans le cadre de la Section d'études féministes du Congrès de l'Acfas 1992, 1993)
Keywords: DIG; amériques; arts; discipline; femmes* artistes; montréal; musique; québec; régions géographiques; témoignage

Y a-t-il une musique virile ? - Panneton, Isabelle (Les Bâtisseuses de la Cité : actes du Colloque Les Bâtisseuses de la Cité dans le cadre de la Section d'études féministes du Congrès de l'Acfas 1992, 1993)
Keywords: DIG; amériques; arts; discipline; femmes* artistes; montréal; musique; québec; régions géographiques; témoignage

L'importance des femmes dans la vie musicale montréalaise entre les deux guerres : mythe ou réalité ? - Paul, Hélène (Les Bâtisseuses de la Cité : actes du Colloque Les Bâtisseuses de la Cité dans le cadre de la Section d'études féministes du Congrès de l'Acfas 1992, 1993)
Keywords: 1900-1999; 1910-1919; 1920-1929; 1930-1939; DIG; amériques; arts; discipline; femmes* artistes; montréal; musique; périodes historiques; régions géographiques; thématiques; travail

La création musicale des femmes au Québec - Lefebvre, Marie-Thérèse (Les éditions du remue-ménage, 1991)
Connues principalement comme pédagogues et interprètes, les femmes en musique ont mis du temps à se faire reconnaître dans le domaine de la composition. C’est ce volet encore ignoré de notre histoire que La Création musicale des femmes au Québec nous fait découvrir, depuis l’apport des communautés religieuses en Nouvelle-France jusqu’aux expérimentations électroacoustiques des vingt dernières années, du phénomène culturel de la musique de salon au début du siècle aux performances multimédias de nos contemporaines…
https://www.editions-rm.ca/livres/la-creation-musicale-des-femmes-au-quebec/
Keywords: 1500-1599; 1600-1699; 1700-1799; 1800-1899; 1900-1999; DIG; amériques; arts; biographie; discipline; femmes* artistes; femmes* compositrices; musique; périodes historiques; québec; régions géographiques; thématiques; travail